Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Transform: $$ F(s) = \frac{2s^2 + (a-6b)s + a^2 - 4ab}{(s^2-a^2)(s-2b)} $$

My steps: $$ F(s) = \frac{2s^2 + (a-6b)s + a^2 - 4ab}{(s+a)(s-a)(s-2b)} $$ $$ = \frac{A}{s+a} + \frac{B}{s-a} + \frac{C}{s-2b} + K $$ $$ K = 0$$

$$A = F(s) * (s+a) $$ at s = -a $$ A = \frac{2a^2 + (a-6b)(-a) +a^2 - 4ab}{4ab+2a^2} $$ $$ A = \frac{a+b}{2b+a}$$

I problems like this (that I've seen) at the step above the fraction would reduce into just a number. In this case, it doesn't and its surprising because I've never seen it happened before. Is there something I am doing wrong here?

share|cite|improve this question
up vote 1 down vote accepted

The routine way is to use the way we get in partial fractions and you correctly noted that. If we set:

$$ \frac{2s^2 + (a-6b)s + a^2 - 4ab}{(s^2-a^2)(s-2b)}=F= \frac{A}{s+a} + \frac{B}{s-a} + \frac{C}{s-2b} $$ then by doing boring :-) handy calculations we can find $A,B$ and $C$. We have then:

$$\frac{-Asa+2Aab+As^2-2Asb+Bsa-2Bab+Bs^2-2Bsb+Cs^2-Ca^2}{(-s+2b)(-s^2+a^2)}$$ Now if we put $s=-a$ in the numerators, we get $A=\frac{a+b}{a+2b}$ and this is what you already got. With the similar approach $s=+a$ for $B$ and $s=2b$ for $C$, we get: $$B=\frac{2a-5b}{a-2b},~~C=\frac{4b^2+2ab-a^2}{a^2-4b^2}$$

share|cite|improve this answer
Needs a TU!! +1 – amWhy Aug 29 '13 at 12:46
What is a TU ?. – 40Plot Aug 29 '13 at 15:36
I'm glad to see you. – user63181 Jan 15 '14 at 20:30

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.